ICTs in Food Consumption Aspects and Activities Allied to Agriculture in India - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The share of activities allied to Agriculture have seen significant increase in the total Agriculture sector gross value added in India over the past few years. In this paper, we review the trajectory of ICTs and digital technologies in the food consumption aspects in India and activities allied to agriculture, particularly livestock and dairying. We also briefly cover the concept of food traceability. Indian startups are rapidly progressing in the food delivery space and a number of startups are covering almost every aspect in the dairying sector. Many startups are also facilitating online cattle trade. All these startups are contributing to the Indian economy. Traceability and other technology led processes have also led to increase in farmer incomes. However, cost affordability and customization for Indian smallholder livestock farmers emerge as the prerequisites for greater digital technology penetration. Telemedicine for livestock health management emerges as an area with a lot of potential to benefit livestock farmers especially in remote and hilly areas with accessibility concerns. Governments can play a proactive role to take these technologies to larger number of farmers by comprehensive digitisation efforts in execution of publicly funded initiatives and also by encouraging startups.
Keywords: 330